Potential of Opuntia cochenillifera (L.) Mill as a Sustainable Forage Resource to Improve Livestock Productivity in Tropical Regions - Rezki Amalyadi (Talenta Publisher, 2025)
Tropical regions are increasingly vulnerable to climate change, which threatens forage availability and livestock productivity due to drought, land degradation, and water scarcity. Opuntia cochenillifera (L.) Mill, a drought-tolerant forage cactus, emerges as a promising solution for resilient and sustainable livestock feeding systems. This review explores its botanical and agronomic characteristics, nutritional profile, and environmental adaptability. Opuntia cochenillifera demonstrates high water-use efficiency, biomass productivity, and nutritional value, making it suitable for arid and semi-arid regions. Its integration into silvopastoral and agroforestry systems enhances environmental sustainability through improved soil health, reduced erosion, and potential carbon sequestration. The cactus also offers economic benefits by lowering feed costs and supporting year-round livestock productivity. However, limitations such as low protein content, potential invasiveness, and high-input management needs remain challenges to be addressed. Future research should focus on genetic improvement, biotechnology applications, and supportive agricultural policies to promote widespread adoption. Overall, Opuntia cochenillifera holds considerable promise for advancing climate-smart and sustainable livestock systems in tropical regions.